Readiness for self-directed learning among medical undergraduate students: Opportunities and challenges - Preethi J Shenoy; Rukmini MS; Rashmi KS (Journal of Krishna Institute of Medical Sciences University)
Background: Self-directed Learning (SDL) entails self-contemplation by students on their individual learning needs and enable them to contrive their goals for learning, recognize authentic learning resources and self-appraise their learning outcomes. As per the new revised Indian medical undergraduate curricula put forth by the National Medical Commission (NMC), SDL has been deemed to be a prerequisite and assigned a predetermined fixed schedule in the timetable. However, very few studies have explored the SDL abilities of the students prior to implementing it. Aim and Objectives: The aim of this study was to measure readiness for SDL of students of the undergraduate medical course and identify SDL needs of the students. Material and Methods: Readiness for SDL was measured among first year undergraduate students by using Self-directed Learning Readiness Scale (SDLRS), developed by Fischer et al., 2000 and later modified and validated for medical students by Hendry & Ginns, 2009. The mean total scores on subcategories, 'Critical Self Evaluation (SE), Learning Self Efficacy (SF), Self-Determination (SD) and Effective Organisation for Learning (OL) were calculated. Results: The observed mean SDLR score was 139.28 ± 13.74 (range 99 – 175). Total scores greater than 129 was considered as readiness for SDL. 77.2% scored greater than 129 indicating high readiness. Mean scores were not significantly different among male and female students. The mean scores in the 4 domains of SE, SF, SD and OL were 20.58 ± 2.91, 73.46 ± 7.87, 17.2 ± 2.33 and 28.2 ± 3.19 respectively. Conclusion: SDL readiness appeared to be high among medical students. The results indicate a need to identify and incorporate pedagogical techniques to nurture and enhance SDL competency among medical students.